1999
DOI: 10.1039/a904968a
|View full text |Cite
|
Sign up to set email alerts
|

Bonding in mixed halogen and hydrogen peroxides

Abstract: The geometries and vibrational frequencies of the hydrogen and halogen peroxides XOOXЈ and the XOO and XO fragments (X, XЈ = H, F, Cl, Br or I) have been studied using non-local density functional theory. The X-O, XЈ-O and O-O bond energies have been calculated and likely dissociation paths for these atmospherically important or potentially important molecules suggested. The sulfur analogues have also been examined. A unified model for these chemically diverse species is presented based on the interaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Subsequent theoretical work [14], however, raised questions concerning the oxidation state of iron in FeO 2 . Using DFT calculations, it was shown that the oxidation state of the Fe ions in the P-phase is not 2+, as in FeS 2 , but has an unexpected valence close to 3+ based on the argument that the O-O distance in FeO 2 is much larger than in free O 2 molecules (1.21Å) [15] or in (O 2 ) 2− ions in typical peroxides (1.49Å) [14,16]. Moreover, high-pressure evolution of the crystal structure and chemical bonding in FeO 2 and its impact on key physical properties remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent theoretical work [14], however, raised questions concerning the oxidation state of iron in FeO 2 . Using DFT calculations, it was shown that the oxidation state of the Fe ions in the P-phase is not 2+, as in FeS 2 , but has an unexpected valence close to 3+ based on the argument that the O-O distance in FeO 2 is much larger than in free O 2 molecules (1.21Å) [15] or in (O 2 ) 2− ions in typical peroxides (1.49Å) [14,16]. Moreover, high-pressure evolution of the crystal structure and chemical bonding in FeO 2 and its impact on key physical properties remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and computational evidence has shown that the O-O bonds of halogen peroxides are shorter than in hydrogen peroxide. 26 For example, the O-O bond in F-O-O-F is only 1.22 Å; making it as short as the double bond in dioxygen. This may be attributed to the σ-attracting and π-donating properties of the halogens.…”
Section: Resultsmentioning
confidence: 99%
“…Some rehybridization is obviously in operation, either by strengthening the bonding or weakening the antibonding O−O interaction. Experimental and computational evidence has shown that the O−O bonds of halogen peroxides are shorter than in hydrogen peroxide . For example, the O−O bond in F−O−O−F is only 1.22 Å; making it as short as the double bond in dioxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Several high-level DFT calculations performed on various relatively simple systems involving first-row transition metals have produced satisfactory agreement between the DFT, LFT, and experimental measurements. Among these, Wang and Schwarz studied first-row transition metal dihalides using the Amsterdam density functional program ADF, Bridgeman and Rothery used the “DeFT” code in the linear combination of Gaussian-type orbitals (LCGTO) framework to study periodic trends in diatomic monoxides and monosulfides of the 3d transition metals, and our recent full-potential linearized augmented plane wave (FP-LAPW) calculations of lattice energies of Me II O oxides (Me = Ca, ..., Zn) have shown a quantitative agreement with experiment and a qualitative agreement with the semiempirical LFT picture. All these studies provide significant support for the physical identity of the LFT and DFT theories.…”
Section: Introductionmentioning
confidence: 81%